STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) APPROACHES USING THEMATIC LEARNING MEDIA TO DEVELOP CRITICAL THINKING - Azka Falaih Rizqiyana; Cris Ayu Setyaningsih; Nurmita Sari (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2021)
Current learning emphasizes the integration of science and technology to face the challenges of the 21st century. Elementary school students experience difficulties in developing critical thinking skills due to the limitations of thematic learning media and appropriate learning approaches. Teachers must support the learning process following the changing times, namely integrating Science, Technology, Engineering, and Mathematics (STEM) into fun learning. The purpose of this study was to determine the effectiveness of the approach stem using thematic learning media in developing the critical thinking skills of elementary school students. This research is a quantitative research using a quasi-experimental method with one-group-pre-test-post-test, which is to see the difference between the pre-test and post-test with 1 class without a control class. Furthermore, the data obtained in this study were in the form of students 'answers to data collection instruments that measured students' critical thinking skills before and after treatment with the approach STEM using thematic learning media. Based on the results of data analysis and discussion, it is concluded that the criteria for improving students' critical thinking skills are in the moderate category, there is a difference in the mean critical thinking skills between the pre-test group, namely before and the post-test group, namely after learning with the approach STEM using thematic learning media and the post-test group, that is, after learning with the approach STEM using thematic learning media has average critical thinking skills better than the pre-test group, namely before learning with the approach STEM using thematic learning media.Keywords: STEM, Learning Media, Thematic, Critical Thinking